Prone positioning ventilation treatment rescuing a patient with chlamydia abortus-induced ARDS diagnosed by next generation sequencing: a case report - Chen, Yi; Lan, Pin; Liu, Lixue; Zhou, Kechun (Frontiers in Medicine, 2024)
Background Chlamydia abortus is a pathogen capable of infecting both humans and animals. In most known cases, this pathogen primarily infects pregnant women, leading to miscarriage and preterm birth. However, it is exceedingly rare for this pathogen to cause pneumonia that progresses to severe Acute Respiratory Distress Syndrome (ARDS). Case introduction We present a case of a 76-year-old male patient who was clinically diagnosed with Acute Respiratory Distress Syndrome (ARDS) caused by Chlamydia abortus and successfully treated. The patient’s condition rapidly deteriorated over six days, evolving from a lung infection to severe pneumonia, ultimately leading to ARDS and sepsis. Initially, he was admitted to a local hospital for a lung infection where routine etiological examinations failed to identify any significant pathogens, and he received only empirical antimicrobial therapy. However, the lung infection was not controlled, and the patient’s condition rapidly worsened, resulting in severe respiratory distress. This necessitated tracheal intubation and assisted ventilation, after which he was transferred to our hospital for treatment. Due to the patient’s family’s inability to afford the cost of ECMO treatment, we adopted a prone positioning ventilation strategy to improve the patient’s ventilation-perfusion matching. Additionally, we performed metagenomic next-generation sequencing on the patient’s bronchoalveolar lavage fluid, which confirmed the infection with Chlamydia abortus. These measures ultimately led to the successful treatment of the patient. Conclusion Chlamydia abortus infection can lead to severe ARDS, necessitating timely diagnosis and active intervention by clinicians. This case highlights the crucial role of metagenomic next-generation sequencing in diagnosing rare pathogens. Timely adoption of prone positioning ventilation can significantly improve ventilation-perfusion matching, effectively treating ARDS caused by Chlamydia abortus. Additionally, the combination of moxifloxacin and piperacillin-tazobactam can treat ARDS caused by Chlamydia abortus.